Esensi Makna Mitsaqon Ghaliza Terhadap Upaya Membentuk Keluarga Sakinah Dalam Al-Qur’an: - Ismaiel Khasan (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
Marriage in Islam recognizes the sentence mitsaqon ghaliza in the Qur'an, which is a very heavy agreement, therefore it must be obeyed by every couple who has entered into a marriage. In family life, Muslims must make religion the foundation and basis for pursuing a life together, religion becomes a guide and guides in various problems of family life in order to create a sakinah family and become part of maintaining a sacred, strong, and sturdy bond in the household. Keywords: mitsaqon ghaliza, religion, sakinah family